Patient experiences during awake mechanical ventilation - Danille Prime; Paul Arkless; Jonathan Fine; Stephen Winter; Dorothy B. Wakefield; Robyn Scatena (Greater Baltimore Medical Center, 2016)
Background: Sedation practices in an ICU have shifted significantly in the past 20 years toward the use of minimizing sedation in mechanically ventilated patients. While minimizing sedation is clearly in the best interest of patients, data are lacking about how this approach affects patients' experiences. Methods: We interviewed mechanically ventilated patients receiving minimal sedation, over a 6-month period in an ICU, in order to explore their emotional, comfort, and communication experiences. Their responses were compared with the responses of their available family members regarding their attitudes and perceptions of the patients' experiences. Results: Seventy-five percent of the patients agreed or strongly agreed that they experienced pain, and 50% agreed or strongly agreed that they were comfortable. Half of the patients agreed or strongly agreed that they preferred to be kept awake. Five patients (31%) indicated that they were frustrated while 17 relatives (89%) agreed or strongly agreed that the patients were frustrated. When controlling for age and gender of respondents, family members perceived higher levels of patient pain (least square [LS] mean [95% CI]: 4.2 [3.7, 4.7] vs. 3.1 [2.5, 3.8]; p=0.022), frustration (LS mean [95% CI]: 4.2 [3.7, 4.6] vs. 3.2 [2.6, 3.9]; p=0.031), and adequate communication with nurses and doctors (LS mean [95% CI]: 3.9 [3.5, 4.4] vs. 3.1 [2.4, 3.7]; p=0.046) than the patients themselves. Conclusion: Patients tolerated minimal sedation without significant frustration while mechanically ventilated despite experiencing discomfort. Patient and family member perceptions of the patient experience may differ, especially in regards to pain and frustration. The use of a communication tool can facilitate understanding of patient experiences and preferences.